Physical and psychological effects of different temperature-controlled breast prostheses on patients with breast cancer during rehabilitation: a randomized controlled study (CONSORT). Issue 13 (March 2020) - Qiu, Jiajia; Tang, Lichen; Huang, Lijin; Hou, Shengqun; Zhou, Jie
Abstract: Background: Breast loss causes negative influence on women physically, psychologically, and socially. Breast prosthesis can improve patient's figure externally, increase self-confidence, thus improving quality of life (QOL). Prospective study of different breast prostheses has not yet been performed in China. Our objective was to evaluate the QOL of patients wearing different types of breast prostheses and to compare the physical and psychological effects of different temperature-controlled breast prostheses on patients. Methods: Thirty patients with breast cancer were recruited through the Yankang E-follow-up Platform at the Department of Breast Surgery of Fudan University, Shanghai Cancer Center and were randomized into either intervention or control group. Random number tables were used in this study for randomization. In the first 6 weeks of the study, self-adhesive breast prostheses and conventional breast prostheses had been used in the intervention and control group, respectively. In the later 6 weeks, the breast prostheses used were switched into another kind. Several dimensional parameters including skin conditions, breast prosthesis knowledge, breast prosthesis knowledge, QOL, and body image were examined by different questionnaires in the end of both 6th and 12th week. Results: There were no significant difference in QOL and body image between the 2 groups during 6th and 12th week. At the 6th week of the study, patients of the intervention group preferred to the self-adhesive breast prosthesis, indicating that the self-adhesive breast prosthesis seemed more likely to feel like part of their body, while prosthesis cleaning remaining their biggest concern. At the end of 12th week, in comparison with the number at 6th week, more patients in both groups were willing to choose self-adhesive breast prosthesis. Conclusions: We conclude that women are satisfied with the temperature-controlled breast prosthesis and are more willing to choose self-adhesive breast prostheses although cleaning remains a problem. In China, patients still lack information about breast prostheses. Therefore, specialist breast nurses should provide comprehensive information about breast prostheses, assist patients in selecting suitable breast prostheses, collect feedback about the prostheses, and reduce each patient's physical and mental discomfort.